Stereoscopically Observing Manipulative Actions - Ferri, S. (Oxford University Press, 2016)
The purpose of this study was to investigate the contribution of stereopsis to the processing of observed manipulative actions. To this end, we first combined the factors “stimulus type” (action, static control, and dynamic control), “stereopsis” (present, absent) and “viewpoint” (frontal, lateral) into a single design. Four sites in premotor, retro-insular (2) and parietal cortex operated specifically when actions were viewed stereoscopically and frontally. A second experiment clarified that the stereo-action-specific regions were driven by actions moving out of the frontoparallel plane, an effect amplified by frontal viewing in premotor cortex. Analysis of single voxels and their discriminatory power showed that the representation of action in the stereo-action-specific areas was more accurate when stereopsis was active. Further analyses showed that the 4 stereo-action-specific sites form a closed network converging onto the premotor node, which connects to parietal and occipitotemporal regions outside the network. Several of the specific sites are known to process vestibular signals, suggesting that the network combines observed actions in peripersonal space with gravitational signals. These findings have wider implications for the function of premotor cortex and the role of stereopsis in human behavior.